Mitigasi Dampak Psikologis Akibat Bencana Tanah Longsor di Kelurahan Oebufu - Lekekasa, Maria Fransina Febriyanti; Damayanti, Yeni; Wijaya, R. Pasifikus Christa (International Journal Labs, 2025)
The landslide disaster in Amanuban Village, Oebufu, caused huge losses, including loss of land, shelter and infrastructure damage. This research uses a case study approach that aims to identify and describe disaster mitigation carried out in Amanuban Village. Data was collected through semi-structured interviews and documentation and then analyzed using thematic analysis method. Based on the results of the study, it shows that the community experienced psychological impacts in the form of stress and trauma. The disaster mitigation carried out is relocation which includes providing relocation houses and moving residences, emotional support in the form of providing strength to fellow survivors, strengthening social motives with colaboration and role sharing, and increasing the ability to face disasters through socialization, counseling, education, disaster training and disaster simulations. The purpose of this mitigation is to reduce the risk of casualties, loss of property, loss of shelter and prevent psychological impacts.